Research on spatial patterns of soil erosion in wind erosion region based on the revised wind erosion equation and partial least squares regression - Huang, Xu-Dong; Li, Yue-Jia; Han, Pei-Pei; Zheng, Ran; Yan, Hua-Jie; Zhao, Pan-Pan; Zhang, Xiao-Li; Feng, Li-Li; Wang, Dong; Zeng, Feng-Juan (Frontiers in Environmental Science, 2024)
Understanding the complex influencing factors of soil erosion is critical for maintaining regional ecological security. The revised wind erosion equation (RWEQ) and partial least squares regression (PLSR) model were used to reveal the primary factors affecting soil erosion. The results indicate that the proportion of mining land, meteorological indicators, and mean square deviation of slope difference were positively correlated with the soil erosion area, intensity and severity. The proportion of grassland and forest land was negatively correlated with the soil erosion area, intensity and severity. The mean square deviation of slope difference, mean square deviation of difference in elevation, and proportion of urban land use contributed the most to the soil erosion severity index, with variable importance in projection (VIP) scores of 1.45, 1.35, and 1.3, respectively. The mean square deviation of slope difference, proportion of urban land, and mean square deviation of difference in elevation contributed the most to the soil erosion area, with VIP scores of 1.4, 1.13, and 1.12, respectively. Based on the results of the RWEQ model, the wind erosion area was 8439.3 km 2 in 2018, accounting for 54.3% of the total area of the planning area, and mild erosion, moderate erosion, intense erosion, very intense erosion, fierce erosion accounted for 18.22%, 11.43%, 11.78%, 10.16%, and 2.74% of the total wind erosion area, respectively. The results provide new insights into wind erosion and the influences of weather conditions and human influences which can guide regional soil and water conservation planning in wind erosion regions.